Are self-identified Christian fundamentalists really more supportive of capital punishment? Exploring the relationship between fundamentalism and death penalty attitudes. Issue 4 (1st October 2016) - Lytle, Robert; ten Bensel, Tusty
Abstract: Christian fundamentalism has often been linked to death penalty support, despite mixed results across more than a decade of empirical studies. More recently, a line of research has emerged that has called for a reconceptualization of fundamentalism as harsh and rigid, instead of being more a multifaceted concept. In the spirit of this call, we investigated the relative importance of Christian fundamentalism on death penalty attitudes when compared with non-religious social attitudes. Using 1, 560 respondents from the 2008 General Social Survey data, we found self-identified Christian fundamentalism, though not biblical literalism or religious denomination, remained a significant predictor of death penalty attitudes when attitudes toward LGBT marriage equality were included in the model. Unexpectedly, white women who endorsed LGBT marriage equality were also more likely to support the death penalty. Based on our findings, we discuss implications and areas for future research.